Analisis Komparasi Algoritma Machine Learning untuk Sentiment Analysis (Studi Kasus: Komentar YouTube “Kekerasan Seksual”) - Soemedhy, Chandra Ayunda Apta; Trivetisia, Nora; Winanti, Nawang Anggita; Martiyaningsih, Dwi Puspa; Utami, Tri Wulandari; Sudianto, Sudianto (Politeknik Harapan Bersama, 2022)
Cases of sexual violence in the last decade have been rampant in Indonesia. Cases of sexual violence are increasingly exposed, along with the increasing use of social media. One of them is violence against women. Cases of sexual violence often cause various kinds of stigma in the community, so this study aims to determine the public's response to cases of sexual harassment using sentiment analysis. The data used is sourced from YouTube comments with the title